Etika Akademis Dalam Pendidikan Islam - Mursal Aziz (UIN Sumatera Utara Medan, 2018)
Academic ethics cannot be separated from the important role of Islamic Education. Islamic education based on the Qur'an and Hadith regulate the relationship of something with other elements, which can ensure harmony, balance, and harmony in life to achieve spiritual progress and happiness. Academic world is expected to provide intelligent solutions to the problems that occur in society universally with guidance to academic ethics. Academic ethics is the essence of scientific activity that takes place in the academic world both in universally applicable educational institutions, such as honesty, rigor, openness, objectivity, humility, willingness to learn and develop, ready to accept criticism, mutual respect and non-discriminatory . Violation of academic ethics is tarnished the world of education, Violations of academic ethics must be analyzed the causes and solutions. As for acts that violate academic ethics should be taken seriously through solutions and prevention efforts.